Analysis of three-dimensional object reconstruction algorithms based on multi-camera arrays - Ruiz, Kevin (My University, 2020)
In this paper, we present a reliable method for three-dimensional object reconstruction based on multi-camera sensor arrays. Camera arrays are an efficient strategy for high-performance imaging and view interpolation. However, challenges can be present such as data size, real-time processing, and the need for automatic calibration. We analyze several methods for three-dimensional object digitalization using camera arrays. This analysis will help us to compare different algorithms and combine several 3D reconstruction methods in a different, efficient and quick way. Experimental results are presented using real and synthetic laboratory objects in terms of objective metrics for 3D reconstruction accuracy. The robustness of these methods for real applications is discussed.
Keywords: Reconstruction algorithm; 3D image processing; Clouds; 3D modeling; Visualization; Campus Tijuana